The Effect of Hard Work in Completing Midwifery Practice Reports on STIKes Kesehatan Baru Students - Delima Panjaitan, Mikka; Tinambunan, Romianna; Palentino Sitorus, Dini (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Currently the implementation of a competency-based curriculum in the Midwifery Diploma III study program has entered the professional education stage. This stage is a very important learning stage in midwifery education, where students begin to apply all the knowledge gained, oriented towards midwifery practice through midwifery services/care to clients with a midwifery approach. midwifery management.The DIII Midwifery Study Program in compiling the Midwifery Practice Report uses the CoC method, namely students starting in semester V compiling case reports taken from cases of continuing midwifery care (CoC) for mothers and babies which cover pregnancy, childbirth, newborns, postpartum and family planning. Where the Midwifery Practice Report or midwifery practice report is one of the requirements that must be met by midwifery level 3 students to get their degree. The main objective is that students graduating from the midwifery study program are expected to have knowledge, skills, attitudes and behavior in their professional field as midwives who are able to provide care within the scope of midwifery practice including independent/autonomous care for girls, young women and adult women before, during pregnancy and afterwards. This means that midwives carry out supervision, provide necessary care and advice to women during pregnancy, childbirth and the postpartum period.Methods: Data collection techniques were carried out by means of in-depth interviews with informants, namely stakeholders including study program leaders, COC coordinating lecturers, supervisors for final assignment reports, midwives at puskesmas as supervisors interviews, document review and participant observation. Research results: Implementation of the CoC method in this Midwifery Practice Report, students can demonstrate their competence to clients through the implementation of midwifery care. Clients are satisfied with the assistance provided by students. The implementation of the Midwifery Practice Report using the CoC method has a positive impact on educational institutions, clients and students can provide real experience of midwifery care. The attitude of hard work in students plays an important role so that competence can be achieved by students. This hard work attitude can be used as a reference in midwifery professional education so that the midwifery practice learning process goes well. Conclusion: With the influence of the students' hard work, the implementation of the Midwifery Practice Report using the CoC method in the D III Midwifery Study Program has been carried out well.